Incidence and Antimicrobial Sensitivity Profiles of Normal Conjunctiva Bacterial Flora in the Central Area of China: A Hospital-Based Study - Tao, Hua; Wang, Juan; Li, Lei; Zhang, Hui-Zhi; Chen, Meng-Ping; Li, Le (Frontiers in Physiology, 2017)
ABSTRACT Objective: To study the distribution and patterns of resistance to antimicrobial agents of normal conjunctival bacteria. Materials and Methods: Conjunctival specimens were collected from 8,224 patients and then cultured, which underwent antimicrobial susceptibility test following standard methods. Patients with infectious symptoms such as erythema or oedema and those using systemic or topical antibiotics within one month were excluded. Results: In this study, the incidence of isolated bacteria was 24.2%. The middle aged group of 41-65 years presented the lowest rate of bacterial isolation which was 19.4%, while the highest isolation rate (83.1%) was found in patients in the age range of 0-6 years. In every age group, the incidence of bacterial isolation in men was higher than that in women. The top 3 most commonly isolated micro-organisms were Staphylococcus epidermidis (39.7%), Streptococcus pneumoniae (4.5%) and Staphylococcus aureus (2.7%), of which about 83.1% Staphylococcus aureus were isolated in the group of 0-6 years. We found that coagulase-negative Staphylococcus (CONS) were more resistant to penicillin, macrolides, clindamycin and sulfonamides with the rate ranging from 57.9% to 90.8%, which were highly susceptible to vancomycin, linezolid, rifampin, tetracyclines and aminoglycosides. Contrasting to CONS, the general resistance rate of Staphylococcus aureus (S.aureus) was significantly lower. Additionally, Streptococcus was susceptible well to the majority of antimicrobial agents, while highly resistant to macrolides and tetracyclines with the rate greater than 80%. Conclusions: In conclusion, our study revealed the incidence and antimicrobial sensitivity profiles of normal conjunctiva bacterial flora in the central area of China, which could be useful in the prevention of ocular infections. Importantly, our data could be used to guide the selection of appropriate prophylactic agents.